Investigating the mechanism and prognosis of patients with disorders of consciousness on the basis of brain networks between the thalamus and whole-brain - Zhang, Jun; Zhang, Hongying; Yan, Fuli; Zhang, Hengzhu; Zhang, Enpeng; Wang, Xingdong; Wei, Min; Pei, Yunlong; Yang, Zhijie; Li, Yuping; Dong, Lun; Wang, Xiaodong (Frontiers in Neurology, 2022)
Purpose: This study aimed to investigate the changes in the functional connectivity between the bilateral thalamus and the whole-brain in patients with severe traumatic brain injury (sTBI) patients suffering from disorders of consciousness (DOC) and to explore their potential prognostic representation capacity. Methods: The sTBI patients suffering from DOC and healthy controls underwent functional magnetic resonance imaging. We defined patients with Extended Glasgow Outcome Score (GOS-E) ≥ 3 as wake group and GOS-E = 2 as coma group. The differences of functional connectivity between sTBI and healthy controls and between wake and coma groups were compared. Based on the brain regions with altered functional connectivity between wake and coma groups, they were divided into 26 regions of interests. Based on Z values of regions of interests, the receiver operating characteristic analysis was conducted to classify prognosis of patients. Results: A total of 28 patients and 15 healthy controls were finally included. Patients who were DOC indicated a significant disruption of functional connectivity between the bilateral thalamus and the whole-brain (FDR corrected, P < 0.0007). The functional connectivity strength (bilateral thalamus to whole-brain) was significantly different between coma patients who went on to wake and those who eventually non-awake at 6 months after sTBI (Alphasim corrected, P < 0.05). Furthermore, the 26 regions of interests had the similar or even better prognostic distinction ability than the admission Glasgow coma score. Conclusions: The thalamus-based system of consciousness of sTBI patients suffering from DOC is disrupted. There are differences in the thalamus-to-whole brain network between wake and coma groups and these differences have potential prognostic characterization capability.